Moral dilemmas reflect professional core values of pharmacists in community pharmacy - Kruijtbosch, Martine (Int J Pharm Pract, 2018)
OBJECTIVES: The aim was to recognise the professional core values in the moral dilemmas of pharmacists in community pharmacy and to customise the descriptions of these values for community pharmacy practice. METHODS: The narratives of 128 moral dilemmas, collected from Dutch PharmD students and early career pharmacists who experienced these dilemmas in practice, were qualitatively analysed. An expert panel deductively coded relevant portions of these narratives with the core values as formulated by the Royal Dutch Pharmacists Association. Other values that emerged were inductively coded and if possible used to further customise the respective core values. KEY FINDINGS: The expert panel identified all four professional core values, that is, commitment to the patient's well‐being (117, 91.4%), reliable and caring (116, 90.6%), pharmaceutical expertise (72, 56.2%) and responsibility to society (30, 23.4%) in the 128 moral dilemma narratives. Thirteen other values that emerged in the analysis could all be used for the customisation of the professional core values in descriptions that better reflect community pharmacy practice. CONCLUSIONS: Professional core values were identified in moral dilemma narratives of pharmacists in community pharmacy and customised for their practice. These customised core values can enable pharmacists to better recognise moral dilemmas in practice. This can add to the advancement of the profession as a pharmaceutical care practice.